2018
DOI: 10.5194/acp-2018-153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The interdecadal worsening of weather conditions affecting aerosol pollution in the Beijing area in relation to climate warming

Abstract: <p><strong>Abstract.</strong> The weather conditions affecting aerosol pollution in Beijing and its vicinity (BIV) in wintertime have worsened in recent years, particularly after 2010. The relation between interdecadal changes in weather conditions and climate warming is uncertain. Here, we analyze long-term variations of an integrated pollution-linked meteorological index (which is approximately and linearly related to aerosol pollution), the extent of changes in vert… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Field studies showed that high PM 2.5 concentrations increase the air stability due to the ARI, leading to decreased PBL height (15, 36, 96, 107, 108). Zhang et al (36) illustrated clearly that the increase in aerosol pollution from the ground can lead to surface cooling by ARI, which facilitates temperature inversions, increases moisture accumulations, and results in extra deterioration of meteorological conditions. A positive feedback cycle involving the interaction between PM, PBL, and water vapor constitutes a self-amplification mechanism to trap PM near the surface.…”
Section: Interactions Among Different Atmospheric Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Field studies showed that high PM 2.5 concentrations increase the air stability due to the ARI, leading to decreased PBL height (15, 36, 96, 107, 108). Zhang et al (36) illustrated clearly that the increase in aerosol pollution from the ground can lead to surface cooling by ARI, which facilitates temperature inversions, increases moisture accumulations, and results in extra deterioration of meteorological conditions. A positive feedback cycle involving the interaction between PM, PBL, and water vapor constitutes a self-amplification mechanism to trap PM near the surface.…”
Section: Interactions Among Different Atmospheric Processesmentioning
confidence: 99%
“…Global warming associated with increasing greenhouse gases in the atmosphere affects the frequency and severity of haze formation by modulating weather conditions. Zhang et al (36) pointed out that the decadal worsening of meteorological conditions can partly be attributed to climate warming. Cai et al (18) found that with future global warming (2050 to 2099) the frequency of unfavorable weather conditions for severe haze events similar to that in January 2013 increases by 50% relative to the historical weather conditions (1950 to 1999), under the scenario of Representative Concentration Pathway (RCP) 8.5 (i.e., radiative forcing of 8.5 W⋅m −2 in 2100).…”
Section: Interactions Among Different Atmospheric Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent and pervasive haze with extremely high levels of PM 2.5 , caused by rapid industrialization and urbanization, frequently engulfs Northern China during wintertime (16). Onlinecoupled meteorology and chemistry models have quantitatively revealed that ARI plays a significant role in the heavy haze formation, with PM 2.5 contribution exceeding 20% (17)(18)(19)(20). Nevertheless, during haze events, high loadings of aerosols in the PBL substantially attenuate solar radiation to suppress photochemical processes and hinder the secondary aerosol formation, offsetting ARI effects on PM 2.5 pollution.…”
mentioning
confidence: 99%
“…Prosperous economic development and intensive expansion have led to a series of heavy aerosol pollution events in recent decades, which are characterized by high loadings of aerosol particles with an aerodynamic diameter less than 2.5 µm (PM 2.5 ) (Guo et al., 2014; Huang et al., 2014). PM 2.5 not only has detrimental impacts on air quality and human health (Chen et al., 2017; Hong et al., 2019), but also influences the regional weather and climate change (Cai et al., 2017; Tao et al., 2012; Zhang et al., 2018). PM 2.5 pollution mainly occurs within the planetary boundary layer (PBL).…”
Section: Introductionmentioning
confidence: 99%